Ta'sir al Ta'liim al Mutamayiz 'ala Nata'ij Ta'allum al Lughah al 'Arabiyyah laday Thalabah al Madrasah al 'Aliyah fi al Ma'had al 'Ashriy al Mutahaddy al Burufisuur al Duktuur Hamka Padang - Novrianti, Windi; Asrina, Asrina; Rahmawati, Rahmawati (Universitas Islam Ahmad Dahlan Sinjai, 2025)
This research aims to explain the influence of differentiated learning on Arabic language learning outcomes in Pesantren Modern Terpadu Hamka Padang. It employs a quantitative apporoach using correlational methods. Data collection tools are observations, questionnaire, interviews, and documents. The results of the research show that: 1) The implementation of differentiated learning is in the 'adequate' category. This means that it is fairly in line with expectations but still needs improvement in the differentiation of content, process, and product. Meanwhile, the learning environment aspect is already good. 2) The average learning outcome of students at Pesantren Modern Terpadu Hamka Padang Senior High School in the affective aspect was 3,32, categorized as 'very good'. 3) Hypothesis testing using simple regression analysis indicates that differentiated learning has influence on learning outcomes, it was known from the F-calculated value being greater than the F-table value in the affective aspects, meaning that Ha was accepted and H0 was rejected. The R Square value shows that differentiated learning contributes 21,2% to affective outcomes. Learning outcomes are primarily influenced by other internal and external factors